Dampak Manajemen Pengetahuan dan Pembelajaran Organisasi terhadap Keunggulan Bersaing: Bukti Empiris pada UMKM Sasirangan di Banjarmasin - Muhammad Hilman Salsabila; Musadieq , Mochammad; Ruhana, Ika (Pascasarjana UIN ANTASARI Banjarmasin, 2025)
This study investigates the influence of knowledge management and organizational learning on the competitive advantage of Sasirangan MSMEs in Banjarmasin, with organizational innovation functioning as a mediating variable. Although previous research has extensively examined these constructs in various industrial contexts, empirical evidence linking knowledge management, organizational learning, innovation, and competitive advantage within culturally based MSMEs—particularly Sasirangan craft enterprises—remains limited. Using a quantitative approach, data were collected from 139 MSME actors through structured questionnaires and analyzed using PLS-SEM. The results indicate that knowledge management and organizational learning significantly enhance organizational innovation, which in turn strengthens competitive advantage. Organizational innovation is also found to significantly mediate the relationship between both antecedent variables and competitive advantage. These findings contribute to the resource-based view and knowledge-based view frameworks by demonstrating that innovation capability is a critical pathway through which internal knowledge processes create competitive value in micro-scale creative industries. Practically, the study highlights the need for structured knowledge management systems, continuous learning mechanisms, and innovation-oriented organizational cultures to support the sustainability and competitiveness of Sasirangan MSMEs in evolving markets.